2020
DOI: 10.3390/ijerph17103689
|View full text |Cite
|
Sign up to set email alerts
|

A Lifestyle (Dietary) Intervention Reduces Tiredness in Children with Subclinical Hypothyroidism, a Randomized Controlled Trial

Abstract: Purpose: Subclinical hypothyroidism (SH) in children and adults is a subject for discussion in terms of whether to treat it or not with respect to the short-term clinical implications and consequences of SH and in the long term. If treatment with thyroxine supplementation is not indicated, no other treatment is available. We investigated whether a lifestyle (dietary) intervention improves or normalizes SH or decreases the presence of Thyroid Stimulating Hormone (TSH) and/or tiredness. Methods: We randomized ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The respondent specifies how often within the last year he/she performed activities related with health, using a 5-point scale: 1 -almost never, 2 -rarely, 3 -sometimes, 4 -frequently, 5 -almost always, and may obtain 24-120 scores. The overall result is then converted into stens, where: 1-4 stens means low, 5-6 mediocre, and 7-10 -high intensity of health behaviours [4].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The respondent specifies how often within the last year he/she performed activities related with health, using a 5-point scale: 1 -almost never, 2 -rarely, 3 -sometimes, 4 -frequently, 5 -almost always, and may obtain 24-120 scores. The overall result is then converted into stens, where: 1-4 stens means low, 5-6 mediocre, and 7-10 -high intensity of health behaviours [4].…”
Section: Methodsmentioning
confidence: 99%
“…A scale devised by B. J. Felton, T. A. Revenson and G. A. Hinrichsen. In the presented study, the Polish version was used as adapted by Zygfryd Juczyński [4]). The questionnaire allows measurement of the extent to which a patient accepts own illness.…”
Section: Acceptance Of Illness Scale (Ais)mentioning
confidence: 99%
See 1 more Smart Citation
“…A few nonrandomized studies found that some QoL benefits were associated with LT4 + LT3 combination therapy ( Table 3 ). In an open-label longitudinal cohort study of a switch to LT4 + LT3, Michaelsson et al (2018) reported that the ThyPRO-39 score fell (indicating a reduction in symptoms of hypothyroidism and better QoL) from 54 [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] at baseline to 15 [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ,…”
Section: Quality Of Life In Patients Treated For Hypothyroidismmentioning
confidence: 99%
“…Other factors that may influence QoL in hypothyroidism include endurance exercise [ 62 ], dietary intervention (a diet with green vegetables, beef, whole milk, and butter) [ 64 ], higher level of antibodies against thyroid peroxidase [ 86 ], the occurrence of severe adverse drug reactions [ 77 ], tablet vs. liquid LT4 formulations [ 44 , 80 ], morning vs. evening LT4 administration [ 58 , 85 ], male gender, the duration of hypothyroidism, frequent visits to the general practitioner before diagnosis, negative experiences with LT4, high expectations of LT4, and the provision of support by the general practitioner [ 104 ]. However, these factors have not been extensively characterized, and their specificity and selectivity remain to be determined.…”
Section: Quality Of Life In Patients Treated For Hypothyroidismmentioning
confidence: 99%